ChemInform Abstract: The Stannides EuPd2Sn2, EuPt2Sn2, EuAu2Sn2, and Eu3Ag5.4Sn5.6 — Structure and Magnetic Properties. Issue 41 (7th October 2014) - Schwickert, Christian; Winter, Florian; Poettgen, Rainer
Abstract The title compounds are prepared by high‐frequency melting of the elements (Nb ampules, 1100 K, 4 h) and characterized by powder XRD, 119Sn and 151Eu Moessbauer spectroscopy, and magnetic measurements.